Sex-Specific Associations Between Leucocyte Measures and Obstructive Sleep Apnea in Han Chinese - Li T; Tan L; Lei F; Tang X (Nature and Science of Sleep, 2024)
Taomei Li, Lu Tan, Fei Lei, Xiangdong Tang Sleep Medicine Center, Mental Health Center, Department of Respiratory and Critical Care Medicine, West China Hospital, Sichuan University, Chengdu, People’s Republic of ChinaCorrespondence: Xiangdong Tang, Sleep Medicine Center, Mental Health Center, Department of Respiratory and Critical Care Medicine, West China Hospital, Sichuan University, 28 Dian Xin Nan Jie, Chengdu, Sichuan, 610041, People’s Republic of China, Tel +86-28-85422733, Fax +86-28-85422632, Email 2372564613@qq.comBackground: White blood cell (WBC) and its subset counts are standard, inexpensive, direct markers of inflammation. Obstructive sleep apnea (OSA) is implicated in changes in inflammation markers, and sex differences are evident in both OSA and inflammation. It is unknown whether sex modulates the relationship between OSA severity and leukocyte measures.Methods: 1222 patients (914 males, 308 females) underwent overnight laboratorial polysomnography and measurement of WBC and its subset (lymphocyte, neutrophil, monocyte) counts. Patients were divided into primary snoring and mild, moderate, and severe OSA groups, and differences in leukocyte parameters were analyzed separately by sex in multivariable analyses.Results: In multiple regression models, higher apnea-hypopnea index (AHI) was independently associated with neutrophil counts only in men, and with higher total WBC, lymphocyte and monocyte counts both in women and men. Further ordinal logistic regression analysis revealed a significant association between AHI and total WBC (OR 1.87, 95% CI 1.09– 3.23) and neutrophil (OR 1.77, 95% CI 1.02– 3.07) counts in men only. Correlation analysis also revealed more robust relationships between leukocyte measures and cardiometabolic risk markers in men than in women.Conclusion: This study provides novel data suggesting a significant association between neutrophil count and OSA severity only in men but not women. Similarly, the relationship between leukocyte parameters and cardiometabolic risk markers were more pronounced in men than women. Our findings suggest a sex-specific impact of OSA on leukocyte measures and on their relationship with indices of cardiometabolic risk.Keywords: obstructive sleep apnea, leukocyte measures, neutrophil, sex differences, cardiometabolic risk factors